On the development of a TRACE model for the study of reflooding in BWR parallel channels - Zakir, Md.Ghulam (My University, 2015)
Abstract In a Loss-Of-Coolant accident in a Boiling Water Reactor, heat generated in the nuclear fuel is not properly removed because of the deterioration of the coolant mass flow rate in the reactor core. This fact leads to an increase of the fuel temperature that can cause damage to the core and leakage of the radioactive fission products. In order to reflood the core and stop the increase of temperature, an emergency core cooling system delivers water under this kind of conditions. The current work is an investigation of how the power distribution between two channels can affect the process of reflooding when the emergency water is injected from the top of the channels. To do so, the thermal-hydraulic system code TRACE has been used. Therefore a TRACE model of the two heated channels has been developed, and three hypothetical cases with different power distributions have been studied.
Keywords: Energi; Grundläggande vetenskaper; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Annan teknik; Energy; Basic Sciences; Sustainable Development; Innovation & Entrepreneurship; Other Engineering and Technologies